Strategi Komunikasi Marketing Produk Perawatan Kulit Bloomka dalam Menarik Minat Beli Konsumen - Aufa Rizki Fadhilah; Ribka Katheryn Berliana (Mahesa Research Center, 2022)
The level of competition in the realm of online business is becoming increasingly fierce and makes each company's marketing strategy an aspect that determines the sales success of the company. Aspects of the marketing communication strategy of each company show the identity of the goods or services it sells, so that this becomes the identity of a brand that must be controlled by the company in order to meet the expectations of the targeted target market. This study aims to determine the marketing communication strategy of Bloomka skin care products in attracting consumer buying Interest . This study used qualitative research methods. Data was collected by means of interviews, documentation, and observation. The results show that the marketing communication strategy carried out for the target market of Generation Z in the field of beauty will have a greater impact if it involves continuous two-way interAction. However, it needs the support of other marketing strategies such as advertising to increase the number of customers and level of awareness, interactive digital marketing, attractive promotions, admins who can explain in detail person-to-person, and events that attract customers' attention.